THE VALUES OF BUREAUCRACY - Paul du Gay (Oxford University Press, 2005)
This emphasis on the ‘values’ of bureaucracy suggests two further points. First, that bureaucracy is not—as many critics assume—a simple singularity. Rather whatever singularity it is deemed to possess is multiple not monolithic (Minson 1993; Osborne 1994; Adler and Borys 1996). To be more specific, bureaucracy has turned out to be less a hard and fast trans-historical model, but rather what we might describe as a many-sided, evolving, diversified organizational device (du Gay 2000; Courpasson 2000; Kallinikos 2004). Different states, for instance, with varying constitutional arrangements, have all produced recognizably ‘bureaucratic’ administrative apparatuses; but state bureaucracies in the plural, in the sense that they are distinctive and nonreducible. The idea, often propagated in the more dramatic of New Public Management texts, of a single, universal (and now obsolete) bureaucratic regime of public administration is as implausible as the solution proffered to this illusory problem: a global recipe which will deliver a form of ‘post-bureaucratic’, ‘entrepreneurial’ government that is always and everywhere ‘best in world’ (Osborne and Gaebler 1992; Osborne and Plastrik 1997) This in turn suggests, secondly, that an abstract celebration or denunciation of ‘bureaucracy’ makes little sense. To defend or criticize bureaucracy, for instance, requires one to be quite precise about which bureaucratic ethics, capacities and comportments one is seeking to criticise or defend in relation to what specific purposes. Indeed, seen in context, what contemporary anti-bureaucrats represent as the inherently indefensible features of ‘bureaucracy’ per se—whether morally or in terms of practical outcomes—can potentially assume a much more positive character. For instance, the plurality and nonreducibility of state bureaux noted above, is also matched by the plurality of obligation and comportment within them. A senior public administrator working in the institutional milieu of British Central Government, for instance, has traditionally, at least, needed to be, inter alia, something of an expert in the ways of the constitution, a bit of a politician, a stickler for procedure and a stoic able to accept disappointments with equanimity (Chapman 1988; Bogdanor 2001).